Eight sessions of transcranial electrical stimulation for postural response in people with Parkinson's disease: A randomized trial - Beretta, Victor Spiandor [UNESP] (2024)
Background: Impairments in postural responses to perturbation are common in people with Parkinson's disease (PwPD) and lack effective treatment. We recently showed that a single session of transcranial direct current stimulation (tDCS) promotes acute improvement of postural response to perturbation in PwPD. However, the effects of multiple tDCS sessions remain unclear. Research question: What is the efficacy of eight sessions of anodal tDCS on postural responses to external perturbation in PwPD? Methods: Twenty-two PwPD participated in this randomized, double-blind, parallel-arm, and sham-controlled study. Participants were randomly distributed into active (a-tDCS; n=11) or sham stimulation (s-tDCS; n=11). Eight tDCS sessions were applied over the primary motor cortex (M1), with the a-tDCS group receiving 2 mA for 20 minutes. Postural responses to external perturbations were assessed before, 48 hours after, and one month after (follow-up) the completion of tDCS sessions. Primary outcome measures included the onset latency of medial gastrocnemius (MG) muscle and range of center of pressure. Secondary outcomes included electromyography and CoP parameters, and prefrontal cortex (PFC) activity. Results: ANOVA revealed a trend for Group*Moment interaction for MG onset latency (p=0.058). a-tDCS tended to have shorter MG onset latency at post-test (p=0.040; SRM = −0.63) compared to pre-test. For the secondary outcomes, only a-tDCS decreased the time taken to recover balance after the perturbation at post-test and follow-up compared to pre-test (both p<0.001; SRM=-1.42 and −1.53, respectively). Also, only a-tDCS demonstrated lower PFC activity at post-test compared to pre-test (p=0.017; SRM = −0.82) and follow-up (p=0.001). Significance: Eight sessions of tDCS over M1 improved postural response to perturbation in PwPD. Some benefits lasted for at least a month. Neuromuscular and behavioral changes observed after the intervention were accompanied by decreased PFC activity (executive-attentional control), suggesting that tDCS applied over M1 can improve movement automaticity.